Certified in public health program: credentialing public health leaders. Issue 1 (7th March 2016) - Foster, Allison
Abstract : Purpose: – Unlike other health professions, there has historically been no licensing, registration, or certification of public health practitioners to demonstrate their qualification to the public and employers. The purpose of this paper is to outline the rationale for developing public health workforce certification, describes the certification process developed by the National Board of Public Health Examiners (NBPHE), and explains how it is affecting public health education and practice. Design/methodology/approach: – This paper is a narrative review from records of NBPHE. Findings: – The Association of Schools and Programs of Public Health commissioned a formal study of health worker credentialing in 1989 and created a task force in 1999 to determine the need for public health credentialing. Based on input from public health leaders and stakeholders, the NBPHE was formed in 2005 to offer the Certified in Public Health (CPH) examination. The first CPH examination was administered in 2008. Uptake of the CPH was strong the first year (693 examinees), dropped by nearly half (369 examinees) in the second year, and then increased each year through 2015. Part of the increase may be due to eligibility revisions for taking the CPH examination. Eligibility for taking the CPH examination was revised in 2010 to include graduate students in public health and in 2015 to include candidates with a bachelor degree from any field and at least five years of work experience in public health. The NBPHE is piloting open professional eligibility for candidates with no formal education in public health and at least five year's public health work experience. Schools and programs of public health accredited by the Council on Education for Public Health (CEPH) view the CPH examination as a useful tool in curriculum assessment and improvement and for maintaining CEPH accreditation. Several schools and programs of public health have begun requiring all graduate students to take the CPH examination. The CPH credential is also increasingly being used as a hiring factor among employers. Originality/value: – NBPHE's CPH credential is unique in the world. Foreign students graduating with American public health degrees have been taking the exam before returning to leadership roles in their own country. The CPH program described can serve as a model for other nations.